Investigation of EM Radiation Changes in SiC based Converters throughout Device Aging - Pu, Shi; Ugur, Enes; Akin, Bilal; Akca, Hakan (IEEE, 2017)
In this paper, a comprehensive analysis on near field electromagnetic radiation (EMR) of SiC power devices throughout aging is studied. To realize thermally triggered degradation, an accelerated test bench has been built to actively apply power cycles, swing junction temperature and trigger device degradation. The junction temperature of the devices under test (DUT) exposed to 30 degrees C to 170 degrees C swing and after each 250 thermal cycles, the devices are plugged into a Synchronous Buck converter operating in continuous conduction mode. Device near field EMR is recorded by a fixed-to-clipper near field probe and a spectrum analyzer. In parallel, DUT electrical parameter shifts are measured by curve tracer as well. Possible causes of SiC MOSFET degradation are discussed under the light of the experimental result.
Keywords: SIC MOSFET; accelerated aging; near field radiation; synchronous buck converter; curve tracer; HIGH-TEMPERATURE; Engineering